An Effective Method to Predict Low Birth Weight in Indonesia Rural Area - Asyifa Robiatul Adawiyah; Kusharisupeni Djokosujono; Nur Alam; Novita Arie Setiawati (Indonesian Journal of Public Health Nutrition, 2021)
Antenatal care is a compulsory program in Indonesia with minimally 4 times visits, unfortunately, regular Antenatal care visit at Kanjillo health center, South Sulawesi, Indonesia is still low. Most of the LBW in Indonesia born in a rural-areas, where most of the women visit ANC during the third trimester. This study aims to determine the cut-off point of mother’s last trimester pregnancy weight for predicting as well as preventing low birthweight outcomes in the community. The research design was cross-sectional with secondary data taken from the Kanjilo health center, with 150 pregnant mothers visited the health center in 2019, as samples. Anthropometric measurements were used to determine the pregnancy weight in the last trimester as well as the weight of the baby born. Univariate, bivariate, multivariate analysis as well as Receiving Operation Characteristic (ROC) analysis was used. Cut off point of 60.5 kg of pregnancy weight in the third trimester of pregnancy and 0.919 AUC can predict low birth weight. To confirm this method, validation should be done in the community setting in several rural areas.